2015
DOI: 10.1038/ng.3305
|View full text |Cite
|
Sign up to set email alerts
|

Natural alleles of a proteasome α2 subunit gene contribute to thermotolerance and adaptation of African rice

Abstract: Global warming threatens many aspects of human life, for example, by reducing crop yields. Breeding heat-tolerant crops using genes conferring thermotolerance is a fundamental way to help deal with this challenge. Here we identify a major quantitative trait locus (QTL) for thermotolerance in African rice (Oryza glaberrima), Thermo-tolerance 1 (TT1), which encodes an α2 subunit of the 26S proteasome involved in the degradation of ubiquitinated proteins. Ubiquitylome analysis indicated that OgTT1 protects cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
195
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(216 citation statements)
references
References 50 publications
5
195
0
1
Order By: Relevance
“…However, these studies have mainly been restricted to the model plant Arabidopsis [9][10][11][12][13][14] . Many studies have shown that expression of heat shock proteins (HSPs) can improve the tolerance of transgenic plants to heat shock (short exposure to high temperatures) 15 . In particular, HSP101 is required for thermotolerance in plants and has potential as a tool for crop improvements.…”
Section: E T T E R Smentioning
confidence: 99%
“…However, these studies have mainly been restricted to the model plant Arabidopsis [9][10][11][12][13][14] . Many studies have shown that expression of heat shock proteins (HSPs) can improve the tolerance of transgenic plants to heat shock (short exposure to high temperatures) 15 . In particular, HSP101 is required for thermotolerance in plants and has potential as a tool for crop improvements.…”
Section: E T T E R Smentioning
confidence: 99%
“…Similarly, seedling survival and root growth at high temperature for natural populations of Arabidopsis thaliana correlated to temperature parameters at the site of origin (Zhang et al 2015). In rice, the presence of a major quantitative trait locus (QTL) for thermotolerance, TT1, has also been linked to the local temperature profile (Li et al 2015). Such local adaptation may also be seen at the molecular level, as the heat stress response of Arabidopsis and Chenopodium album accessions, as measured by induction of heat shock proteins, was more strongly induced in accessions originating from cooler rather than warmer environments (Barua et al 2008;Zhang et al 2015).…”
Section: Local Adaptationmentioning
confidence: 99%
“…These QTL qSF4 and qSF6, apparently stress-induced were found in Xiushui 09 and IR2061 alleles, respectively and possible to use in breeding rice tolerant to HTS (Cheng et al, 2012). Also, a QTL encoding the α2 subunit of the 26S proteasome was identified in the heat-tolerant wild African rice (Oryza glaberrima) that is involved in the degradation of ubiquitinated proteins and OgTT1 when overexpressed in rice, conferring tolerance (Li et al, 2015b). Selection of rice varieties that flower early in the morning (EMF) is one criterion to avoid daytime HTS and reduce spikelet sterility (GRiSP, 2013).…”
Section: Mapping Of Genetic Loci (Qtl) and Genome-wide Association Stmentioning
confidence: 99%